Retracted: Stability of Iodine in Differently Iodised Salts: Retracted: Stability of Iodine in Iodized Salts - Siddiq, Kalsoom; Samiullah, Muhammad; Rashid, Yamin; Ihsan, Muhammad; Yasir , Muhammad; Ali, Fawad (Pakistan BioMedical Journal, 2022)
Retracted: we are retracting this Article title: Stability of Iodine in Differently Iodised Salts as the authors failed to address the concerns raised by the institute representative Mr. Tauqeer Ahmad. The Corresponding author of this article however admits that their name as included in articles as they have covered the publication fee of this article and they don’t have any significant contribution in this research, which is also not a good/Ethical publication practice. To clarify all these issues, we requested many times that the main author Miss Kalsoom Siddiq should reply but despite of many reminders she didn’t reply any of the email. Hence journal decides to retract the article as a final decision.